Tumor-infiltrating CD20+ B lymphocyte: evaluation and association with clinical and pathological characteristics in oral squamous cell carcinoma: CD20+ B cells in OSCC: Clinical-pathology correlation - Bdaiwi, Ahlam T.; Yousif, Aseel M.; AL Drobie , Ban F.; Abbood Al-Osaighari , Suhair W. (Cellular and Molecular Biology, 2025)
B lymphocyte cells have received considerable attention in recent studies regarding their role in tumor immunity. Tumor Infiltrating B cells (TIBs) are the name that describes the B lymphocyte cells that infiltrate a tumor tissue. Different cellular components interplay in the environment of tumor and modulate the response of antitumor immune dynamically. A Dual role for TIBs is detected in tumor immunity regulation instead of just tumor promotion or inhibition. The present study was performed to evaluate the tumor-infiltrating B lymphocyte and the clinical outcome. Immunohistochemical analysis of B Lymphocytes in stromal/intratumoral regions was performed in 40 OSCC specimens by using CD20 antibodies. Expression of the markers and their relationship with clinicopathological parameters was evaluated by using of Independent t-test and Analysis of Variance (ANOVA) (two-tailed). Data analysis demonstrates a significant association of stromal and intratumoral CD20+ B lymphocyte infiltration with well-differentiated lesions (P < 0.05) and stage I cases (P>0.05). In addition to a significant correlation of stromal infiltration of CD20+B lymphocytes with lymph node metastasis (P=0.01). The results suggest that CD20+ B lymphocytes play an important role in OSCC, where higher infiltration of CD20+ B cells in stromal regions, particularly in cases with lymph node involvement, may be used as a prognostic indicator and may aid in determining whether the use of B lymphocyte as therapeutic targets in OSCC.